Function theory on annuli. Issue 7 (3rd July 2019) - Chai, Fujie; Shen, Wenqiang; Sun, Daochun; Yao, Xiao
ABSTRACT: In this paper, we obtain a local version of Picard's theorem on a sequence of disjointed annuli, which extends the classical Picard's theorem of entire functions. Furthermore, we study the local version of Picard's theorem, Borel's theorem, Nevanlina's five value theorem and uniqueness theorems in classP .